Ankyloglossia as a risk factor for maxillary hypoplasia and soft palate elongation: A functional – morphological study. (10th October 2017) - Yoon, A. J.; Zaghi, S.; Ha, S.; Law, C. S.; Guilleminault, C.; Liu, S. Y.
Structured Abstract: Objectives: To characterize associations between restricted tongue mobility and maxillofacial development. Setting and Sample Population: Cross‐sectional cohort study of 302 consecutive subjects from an orthodontic practice. Material and Methods: Tongue mobility (measured with tongue range of motion ratio [TRMR] and Kotlow free tongue measurement) was correlated with measurements of the maxillofacial skeleton obtained from dental casts and cephalometric radiographs. Results: Tongue range of motion ratio and Kotlow measures of restricted tongue mobility were associated with (i) ratio of maxillary intercanine width to canine arch length, (ii) ratio of maxillary intermolar width to canine arch length and (iii) soft palate length. Restricted tongue mobility was not associated with hyoid bone position or Angle's skeletal classification. Conclusions: Restricted tongue mobility was associated with narrowing of the maxillary arch and elongation of the soft palate in this study. These findings suggest that variations in tongue mobility may affect maxillofacial development.